Pengaruh Profitabilitas, Ukuran Perusahaan dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Plastik dan Kemasan Yang Terdaftar Di BEI Tahun 2018 - 2022 - Idrus Can; Ingra Sovita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to examine the effect of profitability, company size, and capital structure on company value. The population in this study is plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange during the observation period 2018 - 2022. This research was conducted on plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange using a quantitative approach. The data analysis technique used is multiple linear regression analysis processed using the SPSS program version 21. The results of this study show that profitability has a positive and insignificant effect on company value, company size has a negative and significant effect on company value, capital structure has a positive and significant effect on company value. Simultaneously profitability, size of the company and capital structure affects the value of plastic and packaging sub-sector companies listed on the IDX 2018 - 2022